Factor analysis of SMEs entering foreign markets: the case of Taiwanese SMEs in Vietnam. (2nd March 2020) - Hsu, Kuei-Ying; Fu, Hsin-Pin; Lin, Arthur J.; Ou, Tsung-Yin
Internationalisation is an important issue for firms, especially small and medium enterprises (SMEs), as compared to large enterprises, SMEs possess limited internationalisation experience and face unknown risks due to limited resources. However, if SMEs understand the determinants for entering into a foreign market and their relative importance, they could deploy their relatively limited resources optimally and maximise the success of entering the global market. Through literature review, this study proposed a three-level factor hierarchical table of SMEs entering foreign markets based on the dynamic capabilities framework. Through expert questionnaires, factor weights were obtained by using a fuzzy analytic hierarchy process (FAHP), and the advantages of the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method were then used to objectively identify six critical success factors (CSFs). The results can be used as reference for Taiwanese SMEs to optimise their decision-making and resource allocation processes for entering into foreign markets.